Screening for diabetes and hypertension in adult dental patients: the experience in a Nigerian dental center - Nnawuihe, Ukachi Chiwendu; Adelusi, Emmauel Adetolu; Salami, Afolake Shakirat; Adebayo, Ezekiel Taiwo; Ahaji, Lilian Ejije (Frontiers in Dental Medicine, 2024)
Objectives: To examine the presentation of Hypertension and Diabetes mellitus in dental patients.Methods: Dental patients were screened for Hypertension and elevated blood sugar using sphygmomanometer and glucometer respectively.Results: A total of 102 males and 129 females participated in the study. Participants who reported a history of Hypertension and Diabetic mellitus were 69 (29.9%) and 20 (8.7%) respectively. Compliance with taking hypertensive and Diabetic medications as advised by a clinician was reported by 68.0% and 85.0% of known Hypertensives and Diabetics respectively out of whom 29.8% had uncontrolled hypertension and 29.4% high blood sugar in the diabetic range (˃200mg/dl). In patients with no history of the diseases, 42 (25.9%) had elevated blood pressure while 5 (2.4%) had high blood sugar in the diabetic range. The prevalence of hypertension was 37.3% and high blood sugar in the diabetic range was 5.2% in the sample.Diabetics were 31 times more likely to be hypertensives than non-diabetics (Odds ratio [OR] =31.06, 95% CI: 5.68 -169.98, p = <0.001).Screening was helpful in detection of undiagnosed cases and suboptimal control of both diseases in patients. Recommendations for dental practice guidelines include routine screening with mandatory screening for hypertension in diabetic patients.